Band renormalization and spin polarization of MoS2 in graphene/MoS2 heterostructures. Issue 12 (4th November 2015) - Coy‐Diaz, Horacio; Bertran, François; Chen, Chaoyu; Avila, José; Rault, Julien; Le Fèvre, Patrick; Asensio, Maria C.; Batzill, Matthias
Abstract : Transition metal dichalcogenides exhibit spin–orbit split bands at the K‐point that become spin polarized for broken crystal inversion symmetry. This enables simultaneous manipulation of valley and spin degrees of freedom. While the inversion symmetry is broken for monolayers, we show here that spin polarization of the MoS2 surface may also be obtained by interfacing it with graphene, which induces a space charge region in the surface of MoS2 . Polarization induced symmetry breaking in the potential gradient of the space charge is considered to be responsible for the observed spin polarization. In addition to spin polarization we also observe a renormalization of the valence band maximum (VBM) upon interfacing of MoS2 with graphene. The energy difference between the VBM at the Γ‐point and K‐point shifts by ∼150 meV between the clean and graphene covered surface. (© 2015 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim) Abstract : The authors show that the electronic properties of van der Waals materials are modified in heterostructures. Compared to free MoS2 surfaces the valence band dispersion of MoS2 is altered by a single graphene adlayer. Furthermore, spin polarization of the spin–orbit split bands in MoS2 is observed at the graphene interface.